Neurodevelopmental disorders as a risk factor for temporomandibular disorder: evidence from Mendelian randomization studies - Wu, Xueqiang; Li, Zefang; Cui, Yiping; Yan, Zhaojun; Lu, Tingting; Cui, Song (Frontiers in Genetics, 2024)
Objective: This study aims to clarify the incidence rate of temporomandibular joint disease in patients with mental disorders Methods: Data extracted from the Psychiatric Genomics Consortium (PGC) and FinnGen databases employed the Mendelian Randomization (MR) method to assess the associations of three neurodevelopmental disorders (NDDs)—Attention-Deficit/Hyperactivity Disorder (ADHD), Autism Spectrum Disorder (ASD) , and Tourette's Disorder (TD)—as exposure factors with Temporomandibular Disorder (TMD). The analysis used a two-sample MR design, employing the Inverse Variance Weighted (IVW) method to evaluate the relationships between these disorders and TMD. Sensitivity analysis and heterogeneity assessments were conducted. Potential confounding factors like low birth weight, childhood obesity, and body mass index were controlled for. Results: The study found that ADHD significantly increased the risks for TMD (OR=1.2342, 95%CI (1.1448-1.3307), P<0.00001), TMD (including avohilmo)( OR=1.1244, 95%CI (1.0643-1.1880), P=0.00003), TMD-related pain(OR=1.1590, 95%CI (1.0964-1.2252), P<0.00001), and TMD-related muscular pain associated with fibromyalgia(OR=1.1815, 95%CI (1.1133-1.2538), P<0.00001), while other disorders did not show significant causal relationships. Conclusion: This study reveals the elevated risk of various TMD aspects due to ADHD. Furthermore, we discuss the link between low vitamin D levels ADHD and TMD. Future research should address these limitations and delve further into the complex interactions between ADHD, ASD, TD, and TMD.